Freeman Center for intellectual and developmental disabilities: Patient-centered interdisciplinary care - Joshua Smith; Brittany N. Hand; Emily Johnson; Corey Keeton; Lauren Wang (Health Care Transitions, 2023)
Objectives: Adults with intellectual or developmental disabilities (IDD) face substantial barriers to accessing high-quality, patient-centered care. This paper describes the development and evolution of the Freeman Center, an integrated, interdisciplinary center developed using feedback from adults with IDD and their family members. Methods: We evaluated the reach of the Freeman Center services and described the patient population. Results: As of November, 2022, 1068 patients were seen at the Freeman Center. These patients represent about 5 % of all people with IDD in Hamilton County Ohio, where the Freeman Center is located. On average in 2022, the Freeman Center provided approximately 380 primary care visits, 47 psychiatry visits, and 85 combined primary care and psychiatry service visits per month. Conclusions: Patient demographic characteristics are largely consistent with the general population of Hamilton County, indicating patients are representative of the county the clinic primarily serves. Further work is needed to evaluate patient outcomes at the Freeman Center.